The Effect of Growth Opportunity and Profitability on Value of Cosmetic Sub-Sector Companies Listed on IDX in 2018-2022 Period - Fitri, Ninda Aulia; Jaya, Fanlia Prima (Hut Publication Business and Management, 2024)
The purpose of this study is to determine whether growth opportunity and profitability affect the value of cosmetic sub-sector companies listed on IDX for the 2018-2022 period. Growth opportunity is measured by GO or Total Assets (TA) and Price Earning Ratio (PER). Profitability is measured by financial ratios, including Return On Asset (ROA) and Return On Equity (ROE). Company Value is measured by Price Book Value (PBV) and Tobins' Q.The population in this study is all cosmetic sub-sector companies listed on IDX. The sample was taken based on the technique purposive sampling and based on the predetermined criteria, a sample of 6 companies was obtained with a total of 8 companies observed. The analysis method used is multiple linear regression analysis with the SPSS (Statistical Product and Service Solutions) tool.The research results show that growth opportunity significant effect on company value. Profitability does not have a significant negative effect on company value. Growth opportunity and profitability have a significant effect on company value.